1998
DOI: 10.1038/sj.jhh.1000705
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Gordon’s syndrome to the long arm of chromosome 17 in a region recently linked to familial essential hypertension

Abstract: Gordon's syndrome (GS) is a salt-sensitive, hyperkalaemic, familial hypertension syndrome which may masquerade in milder forms as essential hypertension. The response of hyperakalaemia to dietary salt restriction and to mineralocorticoids is heterogeneous, suggesting genetic heterogeneity. In a recently published study using small pedigrees, possible linkage of GS to chromosomes 1 and 17 was described. Studying the largest pedigree so far reported with GS, and using fluorescentlabelled microsatellite markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Another explanation may be that WNK4 affects ROMK expression in an isoform-specific manner. In the rat, ROMK isoforms [1][2][3] are differentially expressed along the nephron, with ROMK1 the predominant isoform in the collecting duct. 19 It is also notable that hyperkalemia in type 2 Bartter's usually occurs with subjects with gene deletions removing isoforms 2 and 3.…”
Section: Golbang Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation may be that WNK4 affects ROMK expression in an isoform-specific manner. In the rat, ROMK isoforms [1][2][3] are differentially expressed along the nephron, with ROMK1 the predominant isoform in the collecting duct. 19 It is also notable that hyperkalemia in type 2 Bartter's usually occurs with subjects with gene deletions removing isoforms 2 and 3.…”
Section: Golbang Et Almentioning
confidence: 99%
“…1 At least 3 different genetic loci have been identified for this monogenic syndrome with a further locus likely [2][3][4][5][6] (OMIM 145260, ϩ601844, and ϩ605232). Recent collaborative work from the Lifton and Jeunemaitre laboratories has identified 2 of these loci as members of the novel family of serine-threonine kinases WNK4 and WNK1.…”
mentioning
confidence: 99%
“…Indeed, there is some evidence for an hypertension gene nearby. Markers in this region of chromosome 17 have been linked to essential hypertension 8 and Gordon's syndrome, 9 a form of hypertension characterised by salt-sensitivity and hyperkalaemia. Other studies have examined a marker in the human growth hormone gene on chromosome 17 and found evidence of linkage with DBP in males.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%
“…Analysis of PHA II families showing autosomal dominant transmission revealed linkage of PHA II to chromosomes 1q31-q42 and 17p11-q21. 114,115 This is a form of hypertension which most closely mimics essential hypertension and the mild phenotype may leave a large proportion of patients with Gordon's syndrome undiagnosed.…”
Section: Gordon's Syndromementioning
confidence: 99%